Longitudinal 12-Month Follow-Up of a Male Infant with CYP21A2 Compound Heterozygous Genotype in China: A Case Report - Yin, Yi; Huang, Xinyue; Shi, Yun; Huang, Cheng; Yu, Jian; Liu, Qingsong (American Journal of Perinatology Reports, 2025)
Congenital adrenal hyperplasia (CAH), predominantly caused by 21-hydroxylase deficiency (21-OHD), arises from mutations in CYP21A2. This frequently occurs via gene conversion events between CYP21A2 and its pseudogene, leading to impaired 21-hydroxylase activity and subsequent CAH manifestations.We encountered a case of classic CAH, characterized by electrolyte imbalances (hyponatremia: 125.10 mmol/L; hyperkalemia: 7.06 mmol/L), hyperpigmentation, and markedly elevated endocrine marker levels (17-hydroxyprogesterone: 319.91 nmol/L; adrenocorticotropic hormone: 611.00 pg/mL) in a male neonate. Through genetic diagnostics, we identified a maternal-derived deletion of CYP21A2 exons 1–7 combined with paternal-originated compound heterozygous mutations (c.293-13A/C>G in intron 2 and c.332_339 deletion in exon 3). Implementation of early genetic diagnosis revealed 21-OHD, and immediate therapeutic intervention was initiated within 11 days after the birth of the patient. Long-term treatment, including oral hydrocortisone, fludrocortisone, and 0.9% sodium chloride, provided effective clinical control and management, as determined by longitudinal follow-up monitoring of serum electrolyte profiles, endocrine function, and physical development.This case provided critical insights into the genotype–phenotype correlations of classic 21-OHD. Our findings will contribute to precision medicine for managing this rare endocrine disorder during critical infancy periods, and emphasize the need for comprehensive genetic diagnostics and educational values for neonatal 21-OHD care.
Keywords: 21-hydroxylase deficiency; hyponatremia and hyperkalemia; hyperpigmentation; molecular genetic diagnosis; infant; timely therapeutic intervention; follow-up